Essence and Nominalism? Some Critiques and Responses on the Notion of Essence - Espinosa Zárate, Zaida (Acta Philosophica, 2016)
As the concept of essence continues to be a polemical one in metaphysics, this paper is aimed to shed some light on the problems that have been raised around it by contrasting the views of two contemporary and analytical philosophers, Reinhardt Grossmann and Fernando Inciarte, who represent opposite positions concerning the question of substance. Analogy, the awareness of the different levels in which philosophical investigation can take place, or the understanding of the last form in living beings as actuality – that leads to its interpretation as a forma formarum –, which are operative throughout the entire philosophy of Inciarte, provide us with convenient tools in order to respond to some objections that have already become common places against essentialism among some analytical philosophers.